Analisis Struktural Cerpen “Seragam” Karya Aris Kurniawan Basuki - Vila Rojatul Jannah; Abdurahman . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to describe the intrinsic structure of the short story “Seragam” by Aris Kurniawan Basuki using a structural approach. The analysis focuses on theme, characterization, plot, setting, point of view, and moral message. The method used is descriptive qualitative with content analysis techniques. The data consist of quotations from the short story related to intrinsic elements. The results show that the story presents themes of friendship, sacrifice, and moral conflict. The narrative structure uses a mixed plot dominated by flashbacks. The main character experiences inner conflict between professional responsibility and friendship values. The rural setting strengthens the humanistic message. The first-person point of view creates emotional closeness between readers and the narrator. The moral emphasizes loyalty, responsibility, and moral integrity in friendship.